Modified sewing machine technique in combination with lens aspiration and anterior vitrectomy for large iridodialysis repair - Kwang Kwok Iu; Nadia Yaacob; Sylves Patrick; Azhany Yaakub (Kugler Publications, 2021)
We describe the management of a large iridodialysis repair using the modified sewing machine technique and lens aspiration in a single setting in an eye with blunt ocular injury. We performed the lens aspiration first followed by iridodialysis repair. The technique was easy and fast, with good postoperative anatomical outcome